The Revitalization of Mandi Marpangir Tradition in Matondang Village, Padang Lawas Regency - Daulay, Ernita; Lubis, Tasnim (Tradition and Modernity of Humanity, 2022)
Mandi marpangir is a tradition to clean body and soul at one day before holy Ramadhan and Eid Mubarak. The purpose is to have blessing during Ramadhan month until the day of Eid Mubarak. The purpose of this research was to describe the tradition, cultural values, and local wisdom of Mandi marpangir. This research focused on revitalizing Mandi marpangir according to customs and traditions in Matondang Village. The location of the research was in Matondang Village, Padang Lawas regency. The informants are residents who live in the Matondang Village. The population objects withdrawal is carried out when the researcher selects the entire population in the research location, namely fountains and rivers, which are the places where people do bathing activities. This research used qualitative descriptive method. The data were observation and depth interview. The results of the research showed that the Mandi marpangir is a tradition with a special sacred value in which the community and its surroundings flock to the shower and river by bringing Pangir to perform the bathing ritual together. The Mandi marpangir tradition begins with pounding together the Pangir that has been boiled or brought by the community, which aims to purify ourselves in welcoming the months of Ramadhan and Eid Mubarak.